Waris Lintas Negara: Problematika Dan Solusi Pembagian Harta Lintas Negara Dalam Perspektif Hukum Islam Dan Hukum Positif - Dewa Sukma Kelana; Agus Gandara; Siah Khosyi’ah; Ahmad Fathonih (PT PUSTAKA CENDEKIA GROUP, 2026)
The phenomenon of globalization has significantly increased the mobility of individuals and assets across national borders, giving rise to complex transnational inheritance cases. This article critically analyzes the problems and solutions of cross-border asset distribution from the perspectives of Islamic Law and Indonesian Positive Law. Using a normative juridical approach with comparative and conceptual methods, this study reveals that transnational inheritance is fraught with conflicts of laws, primarily due to the differing connecting factors in Private International Law, such as lex rei sitae, lex patriae, and lex domicilii. Furthermore, the fundamental differences between the rigid, divinely ordained shares in Islamic inheritance law and the testamentary freedom in Western civil law systems exacerbate legal uncertainty. The findings indicate that the absence of a comprehensive Private International Law codification in Indonesia and the territorial limitations of religious courts create significant hurdles in executing cross-border inheritance. To resolve these issues, this article proposes a dual-track solution: the strategic application of Private International Law principles through international wills, and the utilization of flexible Islamic legal mechanisms such as hibah (inter vivos gifts), wasiat wajibah (mandatory wills), and takharuj (compensatory withdrawal). These solutions aim to provide legal certainty and achieve substantive justice in transnational succession..